Interaction of Scientific Knowledge and Implementation of the Multilateral Environment Agreements in Relation to Digital Sequence Information on Genetic Resources - Kobayashi, Kunihiko; Domon, Eiji; Watanabe, Kazuo N. (Frontiers in Genetics, 2020)
Integration of scientific knowledge into negotiations of the Multilateral Environment Agreements (MEAs) is crucial to effective implementation of those MEAs by ensuring uniformity in their terminology. Recent innovations in the field of biotechnology provoked a discussion over “Digital Sequence Information” (DSI) in fora of several MEAs. In the context of this discussion, the term DSI remains ambiguous and encompasses a wide range of concepts, including, at least, DNA/RNA base sequence data. We focused on how the term “DSI” was regarded in negotiations of the Convention on Biological Diversity and the International Treaty on Plant Genetic Resources for Food and Agriculture, analysed the changes of terminology for DSI in the opinions or views of the Parties in the supreme decision-making bodies of these agreements from the perspective of the MEAs implementation. Based on these efforts we suggest the ways and means to support challenges regarding integration of scientific knowledge into MEAs.